2015
DOI: 10.1111/pcn.12260
|View full text |Cite
|
Sign up to set email alerts
|

Shortened telomere in unremitted schizophrenia

Abstract: Aim:Telomere attrition has been noted in many neuropsychiatric and neurodegenerative syndromes, and may indicate a shared molecular pathology across conditions. We evaluated telomere length in subjects with remitted and unremitted schizophrenia and in control subjects. Methods:We measured telomere length as relative telomere/single-copy gene ratios in subjects with schizophrenia (n = 71) using quantitative real-time polymerase chain reaction. This was compared with relative telomere/single-copy gene ratios in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Smoking and BMI were not examined as potential confounds. Similarly, Kota et al (In press) reported that “unremitted,” but not “remitted,” schizophrenia was associated with short LTL compared to controls. The three remaining studies failed to detect short LTL in schizophrenia.…”
Section: Telomere Length In Psychiatric Illnessesmentioning
confidence: 96%
See 1 more Smart Citation
“…Smoking and BMI were not examined as potential confounds. Similarly, Kota et al (In press) reported that “unremitted,” but not “remitted,” schizophrenia was associated with short LTL compared to controls. The three remaining studies failed to detect short LTL in schizophrenia.…”
Section: Telomere Length In Psychiatric Illnessesmentioning
confidence: 96%
“…Seven studies have assessed LTL in schizophrenia or other psychotic disorders (Fernandez-Egea et al, 2009; Kao et al, 2008; Kota et al, In press; Malaspina et al, 2014 Mansour et al, 2011; Nieratschker et al, 2013; Yu et al, 2008) (Table 2). In one study, LTL was significantly shortened in individuals with schizophrenia and was unrelated to antipsychotic use or duration of illness (Kao et al, 2008).…”
Section: Telomere Length In Psychiatric Illnessesmentioning
confidence: 99%
“…Thus far, cross-sectional studies have reported mixed results. Several investigations found shorter LTL in persons with schizophrenia than in healthy comparison subjects (HCs) (Fernandez-Egea et al, 2009;Kao et al, 2008) or at least in subgroups of individuals with more chronic, severely psychotic, or treatment-resistant illness (Kota et al, 2015;Li et al, 2015;Rao et al, 2016;Yu et al, 2008) (but see (Lin, 2015)), possibly suggesting accelerated biological aging Kirkpatrick et al, 2008). However, one large study reported longer LTL in schizophrenia than in HCs (Nieratschker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not schizophrenic patients possess shorter (Kota et al 2014) or longer (Nieratschker et al 2013) telomere length on chromosomes remains at issue, noting that telomere length is regulated by additional factors such as demographics, diet, vitamin levels, etc. (e.g., Cieslak et al 2014;Malaspina et al 2014).…”
Section: Exercise Amelioration Of Telomeric-shorteningmentioning
confidence: 99%